PKM PENGEMBANGAN DESAIN KEMASAN PRODUK BAGI PELAKU USAHA IE BU PEUDAH DI GAMPONG BARO, KEC. IDI CUT, ACEH TIMUR - Ilham, Muhammad; Rahmadani, Debi; Dandiansyah, Ahmad; Nadya, Yusri; Yusnawati; Andriani, Meri; Arif Adlie, Taufan; Navia, Zidni Ilman (Jurnal Masyarakat Berdikari dan Berkarya (Mardika), 2023)
In this humanitarian project, Community Service (PKM) is the entrepreneur of Ie Bu Peudah, one of Aceh's typical foods. This product is known as one of the popular foods during Ramadan. The ingredients in this product come from wild plants and spices rich in public health benefits. The problem partners face is market demand for this product in the form of Ie Bu Peudah flour. This is due to the lack of public knowledge regarding technology in the packaging of Ie Bu Peudah flour products. Therefore, this activity aims to provide training related to product packaging. This community service activity is carried out through the community empowerment method which consists of three stages: socialization, implementation, and monitoring and evaluation of business actors. The results of this activity show that 90% of the public can understand the packaging of Ie Bu Peudah flour products.